CHALLENGES IN KOREAN READING SKILLS DEVELOPMENT: A CASE STUDY AT UNIVERSITAS MADANI INDONESIA - Oboy; Pudja Hermana; Fitra Jasmine Adefiannisa (Jurnal Multidisipliner Kapalamada, 2025)
This study investigates the difficulties faced by Indonesian learners in developing Korean reading proficiency, focusing on students enrolled in the Korean Language Program at Universitas Madani Indonesia. Using a qualitative exploratory design, data were collected through questionnaires and in-depth interviews with seven selected participants. The findings reveal five major obstacles: insufficient vocabulary knowledge, heavy reliance on translation tools, structural and grammatical challenges, and difficulties understanding various text types. Learners also struggle to identify main ideas due to limited discourse-processing skills. These challenges stem from typological differences between Korean and Indonesian, restricted reading exposure, and inadequate cultural knowledge. The study highlights the need for instruction that integrates vocabulary development, explicit grammar teaching, scaffolded text engagement, and cultural literacy. The results offer important insights for improving Korean reading pedagogy in Indonesian educational contexts.